Assessment of quality of life in cancer patients using anchoring vignettes: comparisons between mixed cancer patients, patients receiving palliative care, and the general population - Hinz, Andreas; Wedding, Ulrich; Schulte, Thomas; Friedrich, Michael; Mehnert-Theuerkauf, Anja; Schnabel, Astrid; Lordick, Florian (Frontiers in Psychology, 2025)
ObjectiveQuality of life (QoL) has become a relevant outcome criterion in oncology in general and in palliative care in particular. The aims of this study were to compare the QoL of cancer patients receiving palliative care with groups of mixed cancer patients and with the general population, and to test whether response shift effects influence the assessment of QoL.MethodsThis study included data from several cross-sectional investigations: one sample of 152 cancer patients receiving palliative care, two samples of patients with mixed cancer diagnoses (n > 500), and two samples of the general population (n > 1,000). QoL was assessed with the EORTC QLQ-C30 and with two anchoring vignettes for identifying response shift.ResultsQoL was highest in the general population (EORTC QLQ-C30 mean sum score M = 87.4), followed by the mixed cancer patients (M = 70.9) and the palliative care group (M = 58.2). Both groups of cancer patients rated the anchoring vignette, which presented a subject with mainly physical problems, as being healthier than the general population did.ConclusionThe results show in which specific dimensions advanced cancer patients report strong detriments in QoL. The different assessments of the vignettes indicate a response shift effect so that the cancer patients have changed their frames of reference for assessing QoL in such a way that they indicate less severe restrictions. This means that the reductions in QoL in cancer patients, as measured with standard questionnaires, tend to underestimate the true detriments.